Digital Financial Literacy vs. Finfluencer-Driven Herding Behaviour: Evidence from Indonesia’s Young Investors - Saridona, Resa; Ermawati, Wita Juwita; Suprayitno, Gendut (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
Amidst the rapid growth of the Indonesian capital market, low digital financial literacy and the widespread influence of financial social media pose significant risks for Millennial and Gen Z investors. This study analyzes the influence of digital financial literacy and herding behavior on investment decisions, with financial influencers as a moderating variable. A quantitative method using SEM-PLS analysis was conducted with 327 Indonesian millennial and Gen Z investors as respondents. The results show that digital financial literacy has a significant positive influence, while herding behavior is insignificant on investment decisions. Financial influencers were found to strengthen the influence of herding behavior on investment decisions, but did not moderate the relationship between digital financial literacy and investment decisions. The findings suggest that improving digital financial literacy is crucial for rational investment, while the role of influencers in strengthening herding behavior still requires regulatory oversight.